The United States - Sparvero, E.; Chalip, L.; Green, B. C. (Comparative elite sport development. Systems, structures and public policy, 2025)
Throughout the world, governments (especially federal/central governments) have increased their involvement in elite sport development (Grix, 2016; Scheerder, Willem, & Claes, 2017). Except in the United States, governments have created schemes to subsidise elite athletes and their National Governing Bodies (NGBs), have created national training centres, and have funded applied sport science. The United States stands in stark contrast to the trends in elite sport development that are most commonly observed throughout the rest of the developed world insomuch as the federal government has chosen to delegate elite sport development to sport organisations, and to keep itself out of sport.